KONSEP PEMBENTUKAN KEPRIBADIAN ANAK DALAM PERSPEKTIF AL-QUR’AN (Surat Luqman Ayat 12-19) - Sada, Heru Juabdin (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2015)
Moral education or child's personality is an activity to develop all aspects of human personality that runs lifetime and implemented as a venue. In other words, personality or Moral Education of children not only take place in the classroom alone, but can also take place outside the classroom. Personality or Moral Education anywhere and anytime. Personality can be formed through the efforts of systematic and planned, we try mewujutkan formation of the desired personality because personality is formed not by and evenly, but through the process of shelf life. Many factors can influence the formation of personality, good, bad, weak or strong ,. Initial lessons and principles that must be instilled by parents to their children is a belief, an understanding so as not to Allah with anything, because shirk a bad thing and an act of tyranny is real,even including big sin that future perpetrators will be in the punishment by God on Judgment Day. The application of exemplary method (uswah) in children's education is very effective, especially in growing children's affective, and psychomotor aspects. Parents as educators are the best role models in the child's view. Therefore, a child will always take all actions of his parents, both in act and in spoken words.